Informal Housing: The Interaction Between Social Behavior and Urban Space in Bir El Ater, Algeria - GRIB, Aissa; BRAHMI, Sami (Indonesian Journal of Social Science Research, 2024)
The research addresses the issue of informal housing and the as-sociated social and economic challenges in urban communities, focus-ing on Bir El Ater, Algeria. It aims to investigate the causes of informal housing in the city and its impact on the social fabric and community well-being. The study seeks to produce findings that will help stake-holders develop effective and integrated programs to mitigate this phenomenon, enhance social cohesion, and align urban planning with sustainable development goals.The research was conducted in two phases: a theoretical phase followed by fieldwork, including interviews with local officials and urban planning representatives. This approach aimed to diagnose urban planning violations and understand the challenges related to informal housing. The findings revealed that informal housing primar-ily arises from a gap between residents' practices and land and urban legislation, along with inadequate oversight and practical measures.Recommendations include integrating theoretical work with flex-ible practical steps, improving communication between residents and authorities, and enhancing oversight mechanisms. The study empha-sizes the need for sound frameworks to balance urban growth and sustainable development, strengthen partnerships between official entities and civil society, and allocate adequate resources to oversight bodies. Raising awareness among residents about urban laws is cru-cial for reducing violations and improving compliance, ultimately leading to more effective urban planning and development.